Implementasi Pembelajaran Individual Pada Mata Pelajaran Agama Islam di SMP Swasta Al-Washliyah 42 Berastagi - Alfari, Dwi; Hasanuddin, Hasanuddin (Jurnal Manajemen Akuntansi (JUMSI), 2024)
This study aims to explain the Implementation of Individual Learning in Islamic Religion Subjects at Al-Washliya 42 Berastagi Private Middle School. The method used is qualitative, with data collection techniques through observation. Based on the research conducted, the researchers drew the conclusion that: the learning model used is like individual learning which leads to an emphasis on additional learning for each individual student. Based on the results of observations, researchers saw an increase in the level of interest and interest of students in participating in the teaching and learning process in Islamic Religion subjects. Students also feel comfortable during the teaching and learning process because they get additional lessons or the teacher explains individually to students until they understand correctly the material conveyed by the teacher in each teaching and learning process.